Antifungal activity of novel synthetic peptides by accumulation of reactive oxygen species (ROS) and disruption of cell wall against Candida albicans - Maurya, Indresh Kumar; Pathak, Sarika; Sharma, Monika; Sanwal, Hina; Chaudhary, Preeti; Tupe, Santosh; Deshpande, Mukund V.; Chauhan, Virander Singh; Prasad, Rajendra (Peptides, 2011)
In the present work, we investigated the antifungal activity of two de novo designed, antimicrobial peptides VS2 and VS3, incorporating unnatural amino acid alpha,beta-dehydrophenylalanine (Delta Phe). We observed that the low-hemolytic peptides could irreversibly inhibit the growth of various Candida species and multidrug resistance strains at MIC(80) values ranging from 15.62 mu M to 250 mu M. Synergy experiments showed that MIC(80) of the peptides was drastically reduced in combination with an antifungal drug fluconazole. The dye PI uptake assay was used to demonstrate peptide induced cell membrane permeabilization. Intracellular localization of the FITC-labeled peptides in Candida albicans was studied by confocal microscopy and FACS. Killing kinetics, PI uptake assay, and the intracellular presence of FITC-peptides suggested that growth inhibition is not solely a consequence of increased membrane permeabilization. We showed that entry of the peptide in Candida cells resulted in accumulation of reactive oxygen species (ROS) leading to cell necrosis. Morphological alteration in Candida cells caused by the peptides was visualized by electron microscopy. We propose that de novo designed VS2 and VS3 peptides have multiple detrimental effects on target fungi, which ultimately result in cell wall disruption and killing. Therefore, these peptides represent a good template for further design and development as antifungal agents. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Antifungal peptides; Candida albicans; Cell wall; ROS

Positive role of polyunsaturated fatty acids on sustainable crop production against salt stress: an overview - Srivastava, Smita; Yadav, Sagar (Biologia, 2024)
Abiotic stresses have become more severe and capricious due to global warming and varying climatic conditions, with increased temperature reducing the yield of important agricultural crops due to high evapotranspiration, resulting in the increased amount of soil salinization in arid and semi-arid areas, which has become a significant threat that restricts agricultural practices and leads to the overexploitation of cultivation land. One of the crucial environmental elements limiting plant development and yield is salinity. The special effects of salt stress on the superiority of numerous crops have yet to be discovered. Under salinity, plants tend to activate multiple physiological and biochemical mechanisms to overcome the stress by altering their morphology, photosynthesis, water relations, and biochemical adaptations, such as the antioxidative metabolism response and trigger polyunsaturated fatty acids (PUFAs), which act as a biomarker for salinity stress. With the help of PUFAs, which have become popular as all-purpose defenders, decorative techniques have been created to prevent the consequences of saline. The most prevalent PUFAs in plants are those with 18 carbons, specifically 18:1 (oleic), 18:2 (linoleic), and 18:3 (alpha-linolenic) acids which operate as glycerolipids, a source of energy and carbon in triacylglycerol, precursors of numerous bioactive chemicals, stores of extracellular barrier components, and intrinsic antioxidants, modulating cellular membranes and enhancing crop quality and yield. However, limited information about PUFAs and their roles in enhancing crop stress tolerance is available. Therefore, producers and breeders must understand salinity's influence on crop composition to enhance fatty acids under salinity conditions. However, brief work has been reported; this review will help comprehend the role of fatty acids in salinity for food security through the genetic engineering of synthetic genes encoding fatty acids to improve crop stress tolerance and grain quality.
Keywords: Cuticle wax; Membrane lipids; photosynthesis; Polyunsaturated fatty acid; ROS; salt stress; Sensing mechanism; stress tolerance

Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition

Characterization of wound-induced electrical signals and reactive oxygen species in chickpea (Cicer arietinum) - Deshpande, Shweta; Pawar, Shivani; Kumari, Archana (Plant Signaling & Behavior, 2025)
Mechanical damage to plants triggers both localized and systemic responses that activate plant defense mechanisms. Early signaling events include calcium (Ca2+) flux, reactive oxygen species (ROS), and electrical alterations. These signals coordinate downstream defense pathways, enabling plant acclimation to biotic stress. Electrical signaling following wounding/herbivory has been extensively studied in Arabidopsis; however, its dynamics in crop plants such as chickpea (Cicer arietinum) are not well understood. The pattern of the SWP in chickpea was similar to that in Arabidopsis but with a longer repolarization phase and was detectable only within the leaflets. The signals generated by damaging the leaflet were more pronounced, propagated bidirectionally and varied between herbivore-susceptible and tolerant chickpea varieties. The SWP duration is correlated with increased expression of AOS and OPR3 transcripts, which are markers of the stress hormone JA. Additionally, ROS production in wounded chickpea leaflets is associated with increased expression of ROS-generating genes. The use of DPI, an inhibitor of NADPH oxidase, which is responsible for ROS production, inhibited SWP, suggesting the crucial role of ROS in wound-induced SWP. This study provides insight into the interplay between wound-induced electrical signaling and ROS production in chickpea and proposes the measurement of electrical signals as a rapid, noninvasive approach for screening crop cultivars for pest susceptibility and tolerance.
Keywords: Chickpea; Electrical signal; Plant defense; ROS; wound